Digital HR tools and their role in improving the competitiveness of companies - V. V. Degtyareva (Управление, 2021)
The article analyses the transformation processes, the Genesis of which is due to the practice of using digital HR tools in the context of the implementation of the National Program “Digital Economy of the Russian Federation”, and the determinations of the importance that these tools have for solving the problem of improving the competitiveness of a single company. The paper indicates the prerequisites for the introduction of digital tools in the existing methods of personnel management. The author outlines the guidelines for the development of this industry on the basis of the Federal Program “Personnel for the Digital Economy”. The study identifies factors that characterize the transformation of the HR industry due to the impact of digitalization.The paper shows the experience of implementing SAP Success Factors tools, which indicates that this cloud system, including a set of automated solutions for working with personnel, will allow you to manage talents. The multi-functionality of the system ensures the management of human resources through the use of cloud technologies at all stages: from recruitment to the implementation of the company’s personnel policy. The article shows the advantages of the SAP Success Factors system. The expected effects of implementing SAP Success Factors are to increase the operational efficiency of HR and the efficiency of business processes, as well as to expand the experience of employees.The author concludes that the existing methods of personnel Management are being transformed under the influence of digital technologies and, since human resources play a key role in achieving the organization’s goals, their effective use has a positive impact on its competitiveness. The article contains the results with the elements of scientific novelty: range of factors of HR’s transformation under the influence of digitalization and characterization of the relationship between the use of digital tools in the practice of human resource management and the level of its competitiveness are determined by the author.